2022
DOI: 10.1007/s00167-022-07056-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined MPFL reconstruction and tibial tuberosity transfer avoid focal patella overload in the setting of elevated TT–TG distances

Abstract: PurposeObjectives are (1) to evaluate the biomechanical effect of isolated medial patellofemoral ligament (MPFL) reconstruction in the setting of increased tibial tuberosity–trochlear groove distance (TTTG), in terms of patella contact pressures, contact area and lateral displacement; (2) to describe the threshold of TTTG up to which MPFL reconstruction should be performed alone or in combination with tibial tuberosity transfer. MethodsA finite element model of the knee was developed and validated. The model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…16 Both treatment options coexist and potentially can be combined for recurrent patellar dislocation. Berton et al 11 recently demonstrated that combined MPFL reconstruction and TTO avoid focal patellar overload in the setting of elevated TT-TG distances. However, only a few studies have analyzed the results of MPFL reconstruction with and without TTO.…”
Section: Discussionmentioning
confidence: 99%
“…16 Both treatment options coexist and potentially can be combined for recurrent patellar dislocation. Berton et al 11 recently demonstrated that combined MPFL reconstruction and TTO avoid focal patellar overload in the setting of elevated TT-TG distances. However, only a few studies have analyzed the results of MPFL reconstruction with and without TTO.…”
Section: Discussionmentioning
confidence: 99%
“…58 Some scholars have also modeled the muscle as a two-dimensional fiberreinforced structure containing membrane and spring elements. 59,60 Tendons are similar in structure and function to ligaments. Tendons can be modeled with spring elements and hyperelastic material models, with the spring elements being widely used.…”
Section: Muscle and Tendonmentioning
confidence: 99%
“…simplified the muscle model and used spring elements to simulate the muscle 58 . Some scholars have also modeled the muscle as a two‐dimensional fiber‐reinforced structure containing membrane and spring elements 59,60 . Tendons are similar in structure and function to ligaments.…”
Section: Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tibial tuberosity medialization tends to have a greater influence on the patellofemoral contact pressure distribution than MPFL reconstruction. 22 , 26 Tibial tuberosity medialization tends to shift pressure medially, 20 , 22 which is a concern for patients with medial cartilage lesions due to patellar dislocation. 27 …”
Section: Introductionmentioning
confidence: 99%